Transformation on the run—digitising medical education during the covid-19 pandemic - Hong, Wei-Han (Centre for Medical Education (CenMed) Yong Loo Lin School of Medicine National University of Singapore, 2021)
Introduction: The article is a succinct summary of events and process for emergency digitisation and transition to remote teaching during the COVID-19 pandemic. The challenges of such transition included the need for enhanced infrastructure facilities, compliance to directives from regulatory bodies, providing an equivalent learning experience in the virtual learning environment (VLE) and ensuring the end user capacity to utilise the VLE created. Methods: To accomplish this task a suitable instructional design and transition model was utilised to create an integrated Moodle and Microsoft Teams platform as the VLE. The curriculum was recreated in the VLE through review of existing infrastructure and resources, deconstructing the demands of the curriculum, reconstructing the learning experiences of curriculum in VLE and innovating to improve. The end user training was also provided using the same VLE created, which ensured capacity building. Virtual Clinical Assessments (VCA) were created to ensure the completion of assessment tasks. Results: The utilisation of the ACTIONS transition model resulted in the evolution of instructional delivery from a Web Enhanced approach to a customised Web Centric approach and implementation of Virtual Clinical Assessments. Students expressed their satisfaction in the learning experience through VLE, but were anxious about their clinical training and connectivity issues. Conclusion: This transition demonstrated the need of future directions in terms of learner readiness to be more self-directed and self-determined, design thinking for transformation to a Web Centric curriculum, faculty readiness to change and develop the competency of Technological Pedagogical Content Knowledge (TPACK). © 2021 TAPS. All rights reserved.